THE ANALYSIS OF PUTUKREJO VILLAGE GOVERNMENT READINESS IN FORMING BUMDES AS A DEVELOPMENT EFFORTS OF RURAL COMMUNITIES BASED ON CREATIVE ECONOMY - Agung Minto Wahyu; Navilah Laila Wardani; Ega Aditya; Jeni Susyanti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
The purpose of this study is to determine the readiness of the village government in forming BUMDes as well as the factors forming these readiness as an effort to empower rural communities based on creative economy. This study uses qualitative methods with a case study approach. The case study was conducted at BUMDes “Barokah” owned by Putukrejo Village, Gondanglegi District, Malang Regency. The results of the study confirms that the Putukrejo Village Government has a fairly good readiness in forming BUMDes. It is proven by the development of business units that are very helpful in empowering local rural communities. In addition, BUMDes “Barokah” also seeks to empower the community based on creative economy by establishing the tourist attraction, Sumber Sira Market, which is used to manage the products of the community creativity.